Preparation and structural characterization of vulcanized natural rubber nanocomposites containing nickel-zinc ferrite nanopowders - Bellucci, F. S. [UNESP]; Salmazo, L. O. [UNESP]; Budemberg, E. R.; Silva, M. R. da; Rodriguez-Perez, M. A.; Nobre, Marcos Augusto Lima [UNESP]; Job, Aldo Eloizo [UNESP] (Amer Scientific Publishers, 2012)
Single-phase polycrystalline mixed nickel-zinc ferrites belonging to Ni0.5Zn0.5Fe2O4 were prepared on a nanometric scale (mean crystallite size equal to 14.7 nm) by chemical synthesis named the modified poliol method. Ferrite nanopowder was then incorporated into a natural rubber matrix producing nanocomposites. The samples were investigated by means of infrared spectroscopy, X-ray diffraction, scanning electron microscopy and magnetic measurements. The obtained results suggest that the base concentration of nickel-zinc ferrite nanoparticles inside the polymer matrix volume greatly influences the magnetic properties of nanoconnposites. A small quantity of nanoparticles, less than 10 phr, in the nanocomposite is sufficient to produce a small alteration in the semi-crystallinity of nanocomposites observed by X-ray diffraction analysis and it produces a flexible magnetic composite material with a saturation magnetization, a coercivity field and an initial magnetic permeability equal to 3.08 emu/g, 99.22 Oe and 9.42 X 10(-5) respectively.
Keywords: Ferrite; Nanoparticles; Vulcanized Rubber; Nanocomposites; Structural Property; Magnetic Property